Determining the effects of scenario metrics on the performance of dynamic source routing using taguchi approach - Sarahintu, Mazlan; Lee, Muhammad Hisyam; Mohamed, Hazura (Faculty of Science, 2007)

(untitled)
Design and analysis of routing protocols used for mobile ad hoc network (MANET) is currently an active area of research. This paper deals with determining the effects of several scenario metrics on the performance of dynamic source routing (DSR) protocol with regard to routing overhead. The scenario metrics include terrain, network size, pause time, node velocity, transmission range, traÂ±c load, and packet rates. In this paper, Taguchi approach is used to analyze and estimate the effects of the metrics. It is an extension of the author's previous study on the investigations of the effects of three scenario metrics on several performance metrics. It is discovered that network size was the most signifficant factor affecting the response, followed by pause time, node velocity, and finally traffic load.